Membangun Karakter Kepemimpinan Melalui Organisasi Siswa Intra Sekolah (OSIS) - Mujahidin Mujahidin; Muhamad Rizky Malusu (At Tadbir: Journal of Islamic Education Management is published by the Islamic Education Management Study Programme, IAI al Urwatul Wutsqo, Jombang, East Java, Indonesia., 2024)
This research examines the strategies and practices used in building leadership character through the Intra-School Student Organization (OSIS) at Al Malikus Sholeh Sumobito Vocational School, Jombang. This research uses qualitative methods with in-depth interviews and participant observation as data collection techniques. Research findings show that OSIS is an effective means for developing leadership skills, responsibility, teamwork, and moral values ??in students. This research provides good insight for schools and educators to design programs that focus on developing leadership character through OSIS activities.